(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
The formation of relationships is closely related to the communication of the teacher and educator with an individual child, a team of children and teachers. Relationships and communication skills underlie the adaptation of a novice teacher and educator to teaching. They are also, along with knowledge, professional skills and the general culture of the teacher, the main condition for acquiring pedagogical skills.